2018
DOI: 10.1016/j.livsci.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield and urinary-nitrogen excretion of dairy cows grazing forb pasture mixtures designed to reduce nitrogen leaching

Abstract: Milk yield and urinary-nitrogen excretion of dairy cows grazing forb pasture mixtures designed to reduce nitrogen leaching, Livestock Science,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
(36 reference statements)
1
16
0
1
Order By: Relevance
“…PSM in plantain (aucubin and catalpol) have shown to be highest in concentration in autumn, supporting the hypothesis that these terpenoids are responding to cooler temperatures or increased insect pressure late in the milk production season. Anecdotal evidence that the palatability of plantain by livestock is lower in autumn (Bryant et al 2018) is likely to be linked to fluctuations in these compounds, and cow adaptation has been demonstrated to the overcome initial avoidance of plantain (Box et al 2017b). The advantage of high PSM which reduce rumen degradability in autumn may reduce the risk of high urinary N loading during this high risk period (Figure 1) and suggests plantain as a potential forage for reduced N losses.…”
Section: Plant Secondary Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…PSM in plantain (aucubin and catalpol) have shown to be highest in concentration in autumn, supporting the hypothesis that these terpenoids are responding to cooler temperatures or increased insect pressure late in the milk production season. Anecdotal evidence that the palatability of plantain by livestock is lower in autumn (Bryant et al 2018) is likely to be linked to fluctuations in these compounds, and cow adaptation has been demonstrated to the overcome initial avoidance of plantain (Box et al 2017b). The advantage of high PSM which reduce rumen degradability in autumn may reduce the risk of high urinary N loading during this high risk period (Figure 1) and suggests plantain as a potential forage for reduced N losses.…”
Section: Plant Secondary Metabolitesmentioning
confidence: 99%
“…The inclusion of plantain or chicory does not always result in increased urine volumes (Edwards et al 2015;Nkomboni 2017;Bryant et al 2018). Normally animals will adjust their source of water to meet their requirements and increased trough water intakes have been observed by Dodd et al (2018) and Bryant et al (2018) in comparisons between diverse pastures including forbs and standard ryegrass-white clover pastures.…”
Section: Urine Dilution and N Load Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conventional perennial ryegrass (Lolium perenne) and white clover (Trifolium repens) pastures, N loading from urine patches is equivalent to 700-1000 kg N/ha, of which more than 50% can be lost through leaching (Di & Cameron 2002). Animal and lysimeter studies have demonstrated the efficacy of forages such as plantain (Plantago lanceolata) and Italian ryegrasses (Lolium multiflorum) to reduce N losses (Bryant et al 2018;Totty et al 2013;Woods et al 2016). When plantain accounts for 30-50% of the diet of dairy cows, urinary N concentration and estimated N excretion is reduced by more than 20% with no compromise in milk yield per cow compared with conventional ryegrass clover pastures (Woodward et al 2012;Box et al 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…Italian ryegrass is likely to increase in popularity as a pasture species, as it is well suited for helping reduce NO 3 leaching as drainage (Malcolm et al, 2015; Woods et al, 2016; Bryant et al, 2018). However, the results from our study suggest that it may not be a suitable pasture species for grazing in Cd‐contaminated soil due to its high uptake of Cd under the tested conditions.…”
Section: Discussionmentioning
confidence: 99%